Corporate social responsibility in the food industry: Challenges and prospects for improving customer relationships - Vasilev Vasko (BIO Web of Conferences)
This study explores the role of Corporate Social Responsibility (CSR) in enhancing customer relationships within the food industry. It examines how CSR strategies and practices influence consumer trust, satisfaction, and loyalty, while addressing the growing expectations for ethical and sustainable business operations. The research identifies key consumer expectations regarding social and environmental responsibility and analyzes successful CSR initiatives implemented by leading companies in the sector. Furthermore, the study evaluates the impact of these initiatives on customer engagement and long-term relationships. Challenges faced by enterprises in adopting and maintaining effective CSR practices are also discussed, including resource constraints, regulatory compliance, and communication barriers. Based on the findings, practical recommendations are proposed to improve CSR implementation and align it with evolving consumer values. The paper concludes by outlining future trends and opportunities for leveraging CSR as a strategic tool to strengthen customer relationships and drive sustainable growth in the food industry.